Pengaruh Intensitas Curah Hujan Tinggi Terhadap Infiltrasi Air Pada Lahan Dengan Tutupan Permeable - Arifky, Maulid Ilham (Syntax Literate, 2025)
The rapid development of residential and industrial areas in urban regions has reduced water infiltration areas and increased surface runoff due to the use of impermeable pavements. One of the effective solutions to minimize runoff is the application of permeable pavement, such as paving blocks, which can enhance water infiltration into the soil. This study aims to determine the effect of rainfall intensity, paving block geometry, and pavement slope on infiltration capacity, as well as to compare the infiltration performance between Palu sand and Samboja sand as base aggregate materials. The research was conducted by performing infiltration tests on two types of paving block geometries and two sand variations (Palu and Samboja) under different rainfall intensities and surface slopes. The infiltrated water volume was observed in each condition to analyze the influence of these parameters on the infiltration rate and capacity. The results indicate that infiltration capacity is significantly affected by rainfall intensity and paving block shape, where the surface perimeter of the paving plays an important role in enhancing infiltration. Moreover, greater pavement slopes result in higher infiltration volumes. The comparison between sand types shows that Palu sand provides higher infiltration capacity than Samboja sand, due to its larger particle size and lower clay content, allowing easier water percolation. Overall, the use of paving blocks with appropriate geometry and base materials can be an effective strategy to reduce surface runoff in urban environments.